Determinants of the Unemployment Rate in Bali during the COVID-19 Pandemic in 2020 - Diputra, Gde Indra Surya; Arsha, I Made Risma M.; Adiyadnya, Made Santana Putra (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Unemployment is a social problem that hinders economic growth, including in Bali Province. A high unemployment rate has implications for low-income regions. This study aims to analyze the determinants that affect Bali's unemployment rate via projected population indicators, average length of schooling, and life expectancy. The quantitative method was used to examine secondary data from the Central Statistics Agency. The data were analyzed via multiple linear regression. The results show that during the COVID-19 pandemic, the increase in population projections, average length of schooling, and life expectancy directly affected the unemployment rate, with an effect size of 89.3%. Furthermore, simultaneous testing revealed an impact between these three indicators and the unemployment rate in Bali during 2020, especially during the COVID-19 pandemic, with a probability of 0.000. In contrast to the partial results, we found that the unemployment rate was affected only by an increase in the projected population. In contrast, the average length of schooling and life expectancy did not have a direct influence. Thus, the unemployment rate in Bali can be lowered via relevant indicators that local governments and policymakers can evaluate. The synergy of other indicators must be applied to further identify determinants.